Pesticide exposure assessment for surface waters in the EU. Part 1: Some comments on the current procedure. Issue 7 (3rd May 2016) - Bach, Martin; Diesner, Mirjam; Großmann, Dietlinde; Guerniche, Djamal; Hommen, Udo; Klein, Michael; Kubiak, Roland; Müller, Alexandra; Priegnitz, Jan; Reichenberger, Stefan; Thomas, Kai; Trapp, Matthias
Abstract: In 2001, the European Commission introduced a risk assessment project known as FOCUS (FOrum for the Coordination of pesticide fate models and their USe) for the surface water risk assessment of active substances in the European Union. Even for the national authorisation of plant protection products (PPPs), the vast majority of EU member states still refer to the four runoff and six drainage scenarios selected by the FOCUS Surface Water Workgroup. However, our study, as well as the European Food Safety Authority (EFSA), has stated the need for various improvements. Current developments in pesticide exposure assessment mainly relate to two processes. Firstly, predicted environmental concentrations (PECs) of pesticides are calculated by introducing model input variables such as weather conditions, soil properties and substance fate parameters that have a probabilistic nature. Secondly, spatially distributed PECs for soil–climate scenarios are derived on the basis of an analysis of geodata. Such approaches facilitate the calculation of a spatiotemporal cumulative distribution function (CDF) of PECs for a given area of interest and are subsequently used to determine an exposure concentration endpoint as a given percentile of the CDF. For national PPP authorisation, we propose that, in the future, exposure endpoints should be determined from the overall known statistical PEC population for an area of interest, and derived for soil and climate conditions specific to the particular member state. © 2016 Society of Chemical Industry